LINC-10. The Adequate Treatment of Children and Adolescents with Primary Central Nervous System Germ Cell Tumors (CNS GCT) in a Developing Country. (3rd June 2022) - Cappellano, Andréa M; Dassi, Natalia; Mançano, Bruna; Epelman, Sidnei; Almeida, Daniela B; Cavalheiro, Sergio; Dastoli, Patricia A; Seixas, Maria Teresa; Nicácio, Jardel M; Costa, Marcos D; Silva, Frederico A; Aguiar, Simone S; et al.
Abstract: INTRODUCTION: Primary central nervous system germ cell tumors (CNS GCT) are a heterogeneous group of malignancies that can be divided into germinomas and non-germinomatous GCT (NGGCT), accounting for 2-3% of brain tumors in children/adolescents in the Western hemisphere. The study aim is to report the ability to adequately treat Brazilian patients with CNSGCT through a consortium protocol, reporting their treatment, response and survival. Methods: Since 2013, 58 patients with histologic and/or tumor marker (TM) diagnosis of germinoma with/without HCGβ levels ≤200mIU/ml (n=43), five of them between 100-200mIU/ml, received carboplatin/ etoposide (4 cycles) and NGGCT (n=15), received carboplatin/etoposide/cyclophosphamide (6 cycles), all followed by 18Gy ventricular field irradiation and primary site(s) boost. Autologous hematopoietic cell transplant (AuHCT) was undertaken for NGGCT slow responders. Results: Mean age 13.2 years, 42 males. Diagnosis was made by TM (n=19), surgery (n=25) and both (n=12). Two bifocal cases with negative TM and inconclusive biopsy were treated as germinoma. Primary tumor location was pineal (n=30), suprasellar (n=16), bifocal (n=11) and basal ganglia/thalamus (n=1). Eighteen had ventricular/spinal spread. Second-look surgery occurred in seven patients. For the germinoma group, 36 achieved complete responses (CR) after chemotherapy, seven showed residual teratoma/scar. For the NGGCT after 4/6 cycles, six patients showed CR, two failure/progression and seven partial responses (five with negative TM). Two with positive TM underwent AuHCT. Radiotherapy was utilized as described, except in three patients. Four NGGCT patients died (two disease progression, two other causes with no disease). Toxicity was mostly grade 3/4 neutropenia/thrombocytopenia during chemotherapy. At a median follow-up of 40 months, event-free and overall survival was 100% for germinoma and 64.5% NGGCT. Conclusion: The proposed treatment was feasible to be performed in a developing country, with suitable survival even with VFI dose reduction to 18Gy.